Assessing the Predictive Validity of the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES) in Alaska Native and American Indian People. Issue 5 (September 2020) - Lillie, Kate M.; Jansen, Kelley J.; Dirks, Lisa G.; Lyons, Abram J.; Alcover, Karl C.; Avey, Jaedon P.; Hirchak, Katherine; Herron, Jalene; Buchwald, Dedra; Donovan, Dennis M.; McDonell, Michael G.; Shaw, Jennifer L.
Abstract : Objectives: The objective of this study was to examine the predictive validity of the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES) among Alaska Native and American Indian (ANAI) people with an alcohol use disorder. Methods: The sample was 170 ANAI adults with an alcohol use disorder living in Anchorage, Alaska who were part of a larger alcohol intervention study. The primary outcome of this study was alcohol use as measured by mean urinary ethyl glucuronide (EtG). EtG urine tests were collected at baseline and then up to twice a week for four weeks. We conducted bivariate linear regression analyses to evaluate associations between mean EtG value and each of the three SOCRATES subscales (Recognition, Ambivalence, and Taking Steps) and other covariates such as demographic characteristics, alcohol use history, and chemical dependency service utilization. We then performed multivariable linear regression modeling to examine these associations after adjusting for covariates. Results: After adjusting for covariates, mean EtG values were negatively associated with the Taking Steps ( P  = 0.017) and Recognition ( P  = 0.005) subscales of the SOCRATES among ANAI people living in Alaska. We did not find an association between mean EtG values and the Ambivalence subscale ( P  = 0.129) of the SOCRATES after adjusting for covariates. Conclusions: Higher scores on the Taking Steps and Recognition subscales of the SOCRATES at baseline among ANAI people predicted lower mean EtG values. This study has important implications for communities and clinicians who need tools to assist ANAI clients in initiating behavior changes related to alcohol use.